Pengaruh Corporate Social Responsibility, Leverage, Dan Proporsi Komisaris Independen Terhadap Kinerja Keuangan Perusahaan - Nina Nursida (UIR Press, 2017)
This research was aims to examine empirically the influence of corporate social responsibility, leverage, and the proportion of independent commissioners to the company's financial performance. Through purposive sampling techniques acquired 41 companies that follow PROPER and listed on the Indonesia Stock Exchange as a sample. Performed during the observation period of 3 years, namely the period 2011 through 2013. The results showed that for the model 1 only leverage significant effect on short-term profitability (ROE), while the CSR and the proportion of independent commissioners had no significant effect. For model 2 CSR only significant effect on long-term profitability (Tobin's Q), while the leverage and the proportion of independent commissioners had no significant effect.